Climate Smart Agriculture and Climate Information Services Training Needs for Kenya - Kibe, Anthony M.; Kaoga, James O; Wasonga, Oliver Vivian; Otinga, Abigael N (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The era of climate change, associated with changes in seasons and rising temperatures, has contributed to the worldwide decline in agricultural productivity despite the increasing global food demand. Addressing food insecurity challenges will require that Africans embrace innovative technologies in agricultural sector. Therefore, the concept of climate-smart agriculture (CSA) is timely and slowly gaining considerable traction in Africa. Indeed, the concept of CSA is intended to build resilience in agricultural systems as the local farmers express their needs for adaptation and the possibility of mitigation in agricultural growth strategies to support food security. As indicated by Waaswa et al. (2021) CSA presents the opportunity to meet the world increasing food demands in the face of climate variability, and is responsive to the achievement of Sustainable Development Goals 2 and 13 towards achieving food security and combating climate change. During the meeting involving 21 representatives from nine (9) African countries held in Cotonou, Benin at RUFORUM’s Triennial conference on 12-13th Dec 2021, a review was initiated to provide a baseline information on preferred climate-smart agriculture (CSA) practices and existing programmes in institutions of higher learning in the represented countries that included Kenya, Zambia, Ethiopia, Democratic republic of Congo, Benin, Burundi, Uganda, Ghana and Zimbabwe.